2003
DOI: 10.1238/physica.regular.067a00513
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Streaming Instability of Cylindrical Structures in Finitely Conducting Fluids under the Influence of a Radial Electric Field

Abstract: Linear and weakly nonlinear stabilities of two-layer flows between two concentric circular cylinders are investigated. Two different dielectric inviscid fluids are assumed to flow with different velocities in the two separate layers, whose interface is cylindrical. Hence the flow field is assumed to be axisymmetric. The two fluids are influenced by a radial electric field due to surface charges at the interface. The critical magnitude of the electric field is obtained as a function of the velocity difference i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 33 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…Combining the two Eqs. (2.43) and (2.44) following similar arguments as given by Elhefnawy et al [26], one finds the Ginzburg-Landau equation where the symbols Im and Re denote the imaginary and real parts and the upper bar refer to the complex conjugate terms.…”
Section: Analysis Of the Basic Equationssupporting
confidence: 63%
See 1 more Smart Citation
“…Combining the two Eqs. (2.43) and (2.44) following similar arguments as given by Elhefnawy et al [26], one finds the Ginzburg-Landau equation where the symbols Im and Re denote the imaginary and real parts and the upper bar refer to the complex conjugate terms.…”
Section: Analysis Of the Basic Equationssupporting
confidence: 63%
“…He applied the method of strained coordinates for studying the non-linear breakup of capillary jet instability. Elhefnawy et al [25,26] studied the non-linear stability of cylindrical structures of finitely conducting fluids. In their analysis, two non-linear Schrödinger and Klein-Gordon equations are derived.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic instability of an excited horizontal interface supporting surface charge and admitting heat and mass was carried out by Moatimid [2]. Elhefnawy et al [3] studied the instability of finitely conducting fluids in cylindrical geometry under the influence of radial electric field with surface charges at the interface and it was found that dielectric constant plays a distinctive role in the analysis. El-Sayed et al [4] investigated the effect of general applied electric field on conducting inviscid liquid jets instability in the presence of heat and mass transfer taking surface charges into consideration.…”
Section: Introductionmentioning
confidence: 99%